Body/sex/work intimate, embodied and sexualized labour - Wolkowitz, Carol; Cohen, Rachel Lara; Sanders, Teela; Hardy, Kate (Critical perspectives on work and employment, 2013)
Body/Sex/Work focuses on the intimate, embodied and sexualized labour that occurs within body work and sex work. Bringing together an internationally renowned group of academics, it explores, empirically and theoretically, labour processes, workplace relations, regulation and resistance in some of the many work sites that make up the body work and sex work sectors. The book makes a key contribution to research recognising the embodiment of labour and the body, reframing the key questions in critical studies of work and employment.